Characterization of the GGPP synthase gene family in Arabidopsis thaliana - Beck, Gilles; Coman, Diana; Herren, Edgar; Ruiz-Sola, M. Águila; Rodríguez-Concepción, Manuel; Gruissem, Wilhelm; Vranová, Eva (Plant molecular biology, 2013)
Geranylgeranyl diphosphate (GGPP) is a key precursor of various isoprenoids that have diverse functions in plant metabolism and development. The annotation of the Arabidopsis thaliana genome predicts 12 genes to encode geranylgeranyl diphosphate synthases (GGPPS). In this study we analyzed GGPPS activity as well as the subcellular localization and tissue-specific expression of the entire protein family in A. thaliana . GGPPS2 (At2g18620), GGPPS3 (At2g18640), GGPPS6 (At3g14530), GGPPS7 (At3g14550), GGPPS8 (At3g20160), GGPPS9 (At3g29430), GGPPS10 (At3g32040) and GGPPS11 (At4g36810) showed GGPPS activity in Escherichia coli , similar to activities reported earlier for GGPPS1 (At1g49530) and GGPPS4 (At2g23800) (Zhu et al. in Plant Cell Physiol 38(3):357–361, 1997a ; Plant Mol Biol 35(3):331–341, b ). GGPPS12 (At4g38460) did not produce GGPP in E. coli . Based on DNA sequence analysis we propose that GGPPS5 ( At3g14510 ) is a pseudogene. GGPPS–GFP (green fluorescent protein) fusion proteins of the ten functional GGPP synthases localized to plastids, mitochondria and the endoplasmic reticulum, with the majority of the enzymes located in plastids. Gene expression analysis using quantitative real time-PCR, GGPPS promoter - GUS ( β - glucuronidase ) assays and publicly available microarray data revealed a differential spatio-temporal expression of GGPPS genes. The results suggest that plastids and mitochondria are key subcellular compartments for the synthesis of ubiquitous GGPP-derived isoprenoid species. GGPPS11 and GGPPS1 are the major isozymes responsible for their biosynthesis. All remaining paralogs, encoding six plastidial isozymes and two cytosolic isozymes, were expressed in specific tissues and/or at specific developmental stages, suggesting their role in developmentally regulated isoprenoid biosynthesis. Our results show that of the 12 predicted GGPPS encoded in the A. thaliana genome 10 are functional proteins that can synthesize GGPP. Their specific subcellular location and differential expression pattern suggest subfunctionalization in providing GGPP to specific tissues, developmental stages, or metabolic pathways.